EDUKASI FISIKA MATERIAL DI SMAIT DA’ARUL ILMI LAMPUNG: DARI KONSEP KE APLIKASI - Yusril Al Fath; Surya Prihanto; Ahmad Faruq Abdurrahman; Ayu Aprilia; Iqbal Firdaus; Posman Manurung; Suprihatin Suprihatin; Donna Agnesia; Salwa Dian Pertiwi (STKIP Persada Khatulistiwa Sintang, 2025)
ABSTRACTMaterial physics is an important branch of science that studies the properties and applications of various materials from atomic level as the foundation for modern technological development. The importance of this field encouraged the implementation of a socialization activity aimed at improving students’ understanding of the basic concepts and applications of material physics. The activity was attended by 22 participants and consisted of three stages: an initial survey, socialization using the one group pretest–posttest design through interactive and contextual methods, and data evaluation. The average pretest score of 2.22 increased to 3.45 in the posttest, indicating an improvement based on the Likert scale. These results show that the socialization activity contributed positively to enhancing participants’ understanding and interest in the concepts and applications of material physics. The interactive approach used in the socialization proved effective in strengthening participants’ motivation and insight into this field.Keywords: Physics, material, educationABSTRAKFisika material merupakan cabang ilmu penting yang mempelajari sifat dan aplikasi berbagai material dari tingkat atomik sebagai dasar pengembangan teknologi modern. Pentingnya bidang ini mendorong dilaksanakannya kegiatan sosialisasi yang bertujuan meningkatkan pemahaman siswa terhadap konsep dasar dan penerapan fisika material. Kegiatan diikuti oleh 22 peserta dengan tiga tahap: survei awal, sosialisasi menggunakan metode one group pretest–posttest design secara interaktif dan kontekstual, serta evaluasi hasil. Nilai rata-rata pretest 2,22 meningkat menjadi 3,45 pada posttest, menunjukkan peningkatan poin berdasarkan skala Likert. Hasil ini menunjukkan bahwa kegiatan sosialisasi berkontribusi positif dalam meningkatkan pemahaman dan ketertarikan peserta terhadap konsep serta aplikasi fisika material. Pendekatan sosialisasi yang interaktif terbukti efektif untuk memperkuat minat dan wawasan peserta terhadap bidang ini.Kata Kunci: Fisika, Material, Edukasi